OST1‐mediated BTF3L phosphorylation positively regulates CBFs during plant cold responses - Ding, Yanglin (EMBO J, 2018)
Cold stress is a major environmental factor that negatively affects plant growth and survival. OST1 has been identified as a key protein kinase in plant response to cold stress; however, little is known about the underlying molecular mechanism. In this study, we identified BTF3 and BTF3L (BTF3‐like), β‐subunits of a nascent polypeptide‐associated complex (NAC), as OST1 substrates that positively regulate freezing tolerance. OST1 phosphorylates BTF3 and BTF3L in vitro and in vivo, and facilitates their interaction with C‐repeat‐binding factors (CBFs) to promote CBF stability under cold stress. The phosphorylation of BTF3L at the Ser50 residue by OST1 is required for its function in regulating freezing tolerance. In addition, BTF3 and BTF3L proteins positively regulate the expression of CBF genes. These findings unravel a molecular mechanism by which OST1‐BTF3‐CBF module regulates plant response to cold stress.